On the button the significance of an ordinary item - Edwards, Nina (I.B. Tauris, 2012)
What do you use every day that is small and large, worthless and beyond price? It's easily found in the gutter, yet you may never be able to replace it. You are always losing it but it faithfully protects you; sexy and uptight, it is knitted in to your affections or it may give you nightmares. It has led to conflict, fostered and repressed political and religious change and epitomizes the great aesthetic movements. It's Eurocentric, and is found all over the world. On the Button is an inventive and unusual exploration of the cultural history of the button, illustrated with a multiplicity of buttons in black and white and color. It tells tales of a huge variety of the button's forms and functions, its sometimes uncompromising glamour, its stronghold in fashion and literature, its place in the visual arts, its association with crime and death, and its tender call to nostalgia and the sentimental. There have been works addressed to the button collector and general cultural histories, but On the Button links the two, revealing why we are so attracted to buttons, and how they punch way above their weight. It is illustrated with a multiplicity of buttons
Online Ausgabe erschienen bei Bloomsbury Collections: 2019
Keywords: Fashion & society; Buttons; Fasteners; Electronic books